Correlation between patients' age and cancer immunotherapy efficacy. (3rd April 2019) - Wu, Qiong; Wang, Qiuhong; Tang, Xin; Xu, Ran; Zhang, Luzhong; Chen, Xinming; Xue, Qun; Wang, Ziheng; Shi, Rongfeng; Wang, Feiran; Ju, Fei; Zhang, Bo; et al.
ABSTRACT: Background : Although immunosenescence-induced difference on overall immune function and immune cell subsets between younger and older populations has been well characterized, the potential effect of patients' age on the efficacy of immune checkpoint inhibitors (ICIs) remains little known. We performed a meta-analysis to investigate whether age differences play a role in cancer immunotherapy efficacy based on a large amount of clinical data. Methods : We conducted a systematic search of PubMed, Embase and MEDLINE for relevant randomized controlled trials. The primary outcome was overall survival (OS) and progression-free survival (PFS) was secondary outcome. The interaction test was used to assess the heterogeneity of HR between younger and older groups. Results : In total, 19 clinical randomized trials involving 11157 patients were included. The pooled HR for OS was 0.73 (95% CI 0.69–0.78) and 0.63 (95% CI 0.52–0.73) for PFS in younger patients receiving ICIs treatments, when compared with younger patients treated with controls. For older patients treated with ICIs, the pooled HR for OS compared with controls was 0.64 (95% CI 0.59–0.69) and 0.66 (95% CI 0.58–0.74) for PFS. The difference on OS efficacy between younger and older patients treated with ICIs was significant (Pheterogeneity  = 0.025). Conclusions : Immune checkpoint inhibitors significantly improved OS and PFS in both younger and older patients compared with controls, but the magnitude of benefit was clinically age-dependent. Patients ≥65 y can benefit more from immunotherapy than younger patients. Future research should take age difference into consideration in trials and focus on tolerance and toxicity of ICIs in older patients.